Ileocolic intussusception-a rare cause of acute intestinal obstruction in adults - Monteiro, Grancy V.; Paul, Sam (International Journal of Research in Medical Sciences, 2023)
The primary report of intussusception was made in 1674 by Barbette of Amsterdam. It increases the patient’s risk of intestinal obstruction, parietal ischemia, perforation, and peritonitis. Small intestinal submucosal lipomas are an uncommon kind of gastrointestinal tumour. It is a silent disease that occasionally causes gastrointestinal haemorrhage, intussusception, and bowel obstruction. Surgery is frequently required to confirm the diagnosis and rule out an underlying malignancy. We present a case of submucosal lipoma causing enteric obstruction in a young female.